Preparation and optimization of surface stabilized cryptotanshinone nanocrystals with enhanced bioavailability - Zhao, Wenzheng; Ruan, Bohao; Sun, Xiaoyi; Yu, Zhenwei (Frontiers in Pharmacology, 2023)
Cryptotanshinone (CTS) is a plant product extracted from Salvia miltiorrhiza Bunge with various pharmacological significances. In addition to its activities against coronary heart disease, hyperlipidemia, stroke, hepatitis and chronic renal failure, it demonstrates antimetastatic effects. However, its clinical use is limited due to its poor aqueous solubility and oral bioavailability. Herein, CTS nanocrystals were prepared with the precipitation method followed by high-pressure homogenization using Poloxamer 407 as the stabilizer. A stable product was further obtained by lyophilization. The particle size of the CTS nanocrystals was 315.67±11.02 nm, and the zeta potential was near 0 mV. The crystallinity was confirmed by DSC and PXRD. The saturation solubility was substantially increased from 0.97±0.12 µg/mL to 62.29±1.91 µg/mL, and the dissolution rate was also significantly accelerated. A pharmacokinetic study in rats revealed an improvement in oral bioavailability (2.87-fold) with CTS nanocrystals compared to the raw drug. In conclusion, the results of this study suggest a feasible formulation for the oral delivery of CTS.